PERAN PENDIDIKAN KARAKTER DALAM MEMBENTUK KARAKTER GENERASI MUDA DI ERA DIGITAL: STUDI KUALITATIF PADA SEKOLAH MENENGAH DI JAWA TIMUR, INDONESIA - siti durrotul farida; Imron Fauzi (Cendekia Madani Nusantara, 2026)
This study aims to conduct an in-depth analysis of the role of character education in shaping the morals and ethics of the younger generation in the digital era through a descriptive qualitative approach carried out in secondary schools in East Java, Indonesia. By collecting data from in-depth interviews with five teachers and ten students, participatory observations during technology-based learning processes over a three-month period, as well as curriculum document analysis and school activity reports, the findings reveal that integrating character values such as empathy, responsibility, and digital literacy through interactive video-based learning and digital workshops significantly enhances students’ ability to interact ethically in the online environment. Teachers serve not only as technical facilitators but also as moral role models who guide students to avoid risks such as cyberbullying and social media addiction, while the synergy among schools, families, and communities strengthens the formation of holistic character that is adaptive to digital dynamics. The novelty of this research lies in the integration of digital literacy with character education grounded in humanistic-spiritual values inspired by Pancasila, which provides practical implications in the form of recommendations for national teacher training and the development of digital ethics policies by the Ministry of Education, Culture, Research, and Technology to create a young generation with strong integrity amid the global flow of information. This study also emphasizes the urgency of a collaborative approach to optimize technological opportunities while minimizing the threats of moral degradation, as supported by similar findings in other qualitative studies in Indonesia